An Introduction to Gangs and Serious Youth Violence in the United Kingdom. (April 2020) - Densley, James; Deuchar, Ross; Harding, Simon
This article introduces the special issue on UK gangs and youth violence. Written to coincide with the launch of the National Centre for Gang Research at the University of West London, this collection adds the voices of academics who have spent years researching serious violence to a conversation dominated by policymakers and media commentators. The authors examine trends in youth violence and offer a brief history of UK gang research before previewing the contribution of the seven empirical articles dealing with police gang databases, knife crime, county lines drug dealing, contextual safeguarding, offender mental health, gang disengagement and criminal desistance.